2012 Asia-Pacific Symposium on Electromagnetic Compatibility 2012
DOI: 10.1109/apemc.2012.6237932
|View full text |Cite
|
Sign up to set email alerts
|

UWB microstrip antenna based on circular patch topology with stepped feedline and partial ground plane

Abstract: An Ultra Wideband (UWB) microstrip antenna consisting of a circular monopole patch with stepped feed line, with a IOdB return loss bandwidth from 3.50 to 11.20 GHz and maximum VSWR of 1.07 is proposed. This antenna was designed on Rogers 5880 printed circuit board (PCB) with overall size of 31.17 x 40 x 0.787 mm 3 and dielectric substrate Er = 2.2. This antenna operated at UWB frequency and it designed by using CST Software based on the son characteristic impedance for the transmission line model. The antenna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This antenna design is the improvement from [6]. One block was added to the design and it looks like "wing".…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This antenna design is the improvement from [6]. One block was added to the design and it looks like "wing".…”
Section: Antenna Designmentioning
confidence: 99%
“…Previously, the authors have reported on the design of UWB antenna based on the circular patch topology with two block fed by stepped microstrip line and partial ground plane [6]. By optimizing the value of diameter length, 2 blocks dimension, and length of ground plane the antenna can operated with a good return loss which is greater than 10dB from 3.50 to 11.20 GHz and maximum VSWR of 1.07.…”
Section: Introductionmentioning
confidence: 99%
“…A T-slot was introduced in rectangular radiating elements in [17] to enhance the impedance bandwidth of the antenna. As proposed in [18], partial ground plane is used to enhance the impedance bandwidth of the proposed antenna. The effect of a reduced ground plane for ultra-wideband antenna impedance matching was proposed in [19].…”
Section: Introductionmentioning
confidence: 99%